Literature Study of Islamic Values Integration in Biology Subject in SMA/MA (Senior High Schools/Islamic Senior High School) - Zahro', Anisatuz; Muzazzinah, Muzazzinah; Ramli, Murni; Wulandari, Eka (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2022)
Because science, including biology, has a tight relationship with Islamic knowledge, learning biology in schools should not be viewed as a monodisciplinary that stands alone but rather as having an axiological value system tied to other disciplines. This sort of research is literature research that refers to a previously conducted issue and tries to identify the extent to which the integration process of Islamic principles in Biology learning in SMA/MA (Senior High Schools/Islamic Senior High Schools) has been carried out. The data was collected through secondary sources such as credible national and international journal publications published in the Google Scholar database. The findings of this study indicate that the application of the integration of Islamic values in biology learning in SMA/MA can be made through several models, including (1) the Al-Qur'an integration model as a source of inspiration, namely placing the Qur'an at the beginning of learning as an umbrella of knowledge; and (2) the Qur'an integration model as a source of confirmation, namely scientific findings are to clarify what has been stated by the Qur'anABSTRAK: Ilmu sains termasuk Biologi mempunyai hubungan yang erat dengan pengetahuan Islam sehingga pembelajaran Biologi di sekolah semestinya tidak hanya dipandang sebagai monodisiplin ilmu yang berdiri sendiri, tetapi secara aksiologis memiliki sistem nilai yang berkaitan dengan disiplin ilmu lainnya. Jenis penelitian ini merupakan penelitian kepustakaan (literature research) yang mengacu pada suatu topik yang sebelumnya pernah dilakukan yang bertujuan untuk mengetahui sejauh mana proses integrasi nilai-nilai Islam yang telah dilakukan dalam pembelajaran Biologi di SMA/MA. Data yang diperoleh berupa data sekunder yang bersumber pada artikel jurnal nasional maupun internasional yang diterbitkan dalam database Google Scholar. Hasil penelitian ini menunjukkan integrasi nilai-nilai Islam dalam pembelajaran Biologi di SMA/MA, diantaranya adalah (1) model integrasi Al-Qur’an sebagai sumber isnpirasi, yaitu meletakkan Al-Qur’an pada awal pembelajaran sebagai payung pengetahuan; (2) model integrasi Al-Qur’an sebagai sebagai sumber konfirmasi, yaitu temuan dalam sains adalah memperjelas apa yang telah dikermukakan Al-Qur’an.